A comparative assessment of the forces and moments generated at the maxillary incisors between conventional and self-ligating brackets using a reverse curve of Spee NiTi archwire - Sifakakis Iosif; Pandis Nikolaos; Makou Margarita; Eliades Theodore; Bourauel Christoph (Sciendo, 2023)
To compare the intrusive forces and labio-palatal moments generated at the maxillary incisors by a 0.017 x 0.025 inch reverse curve NiTi wire using self-ligating and conventional brackets.